Biopolitics and psychiatrization of life - Caponi, Sandra Noemi (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2015)
ABSTRACT This paper analyze the historical conditions that led to consider that a collection of daily and trivial facts, such as deep sadness, lack of attention of children at school, excessive concerns about work, changes in sleep and appetite patterns, namely, that are common elements of human existence, began to be regarded as indicators of a psychiatric pathology. In other words, I propose to analyze the consolidation of that space of knowledge and intervention that Michel Foucault called medicine of the non-pathological, a medicine where the borders between normal and pathological seem to have been vanished. RESUMO Este artigo analisa as condições históricas que levaram a considerar que uma coleção de fatos diários e triviais, tais como tristeza profunda, a falta de atenção de crianças na escola, as preocupações excessivas com o trabalho, as mudanças nos padrões de sono e apetite, ou seja, fatos que são elementos comuns da existência humana, passaram a ser considerados como indicadores de uma patologia psiquiátrica. Em outras palavras, proponho analisar a consolidação desse espaço de conhecimento e intervenção que Michel Foucault chamou como medicina do não-patológico, uma medicina na qual as fronteiras entre o normal e o patológico parecem ter desparecido quase completamente. Palavras-chave: Biopolítica; Psiquiatria; Patologia; Genealogia; Conhecimento; Normal; Loucura; Degeneração.